2020
DOI: 10.1017/s0022215120002066
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic analysis of the prevalence of International Frontal Sinus Anatomy Classification cells and their association with frontal sinusitis

Abstract: Objectives To determine the radiological prevalence of frontal cells according to the International Frontal Sinus Anatomy Classification in patients undergoing computed tomography of the paranasal sinuses for clinical symptoms of chronic rhinosinusitis, and to examine the association between cell classification and frontal sinusitis development. Methods A total of 180 (left and right) sides of 90 patients were analysed. The prevalence of each International Frontal Sinus Anatomy Classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A total of 56 studies with 11 805 persons were included. All studies 13–66 involved a single population except for two studies 5,67 which recruited two distinct populations in each study. The studies were from 27 countries which can be divided into seven regions specifically Africa, Asia, Australia‐New Zealand‐Oceania, North America, South America, Europe and Middle East.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 56 studies with 11 805 persons were included. All studies 13–66 involved a single population except for two studies 5,67 which recruited two distinct populations in each study. The studies were from 27 countries which can be divided into seven regions specifically Africa, Asia, Australia‐New Zealand‐Oceania, North America, South America, Europe and Middle East.…”
Section: Resultsmentioning
confidence: 99%
“…Seth et al [36] reported the prevalence of supra bulla frontal cells in study was 21.1%. This prevalence rate was higher than those in the North American and Vietnamese groups, which were 5.5% and 4.3% respectively [35,37].…”
Section: % Studymentioning
confidence: 92%
“…Multiple studies investigated frontal cells’ prevalence based on IFAC within different populations [ 8 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table 1 ). Similarly, other studies investigated their prevalence based on the Kuhn classification [ 28 , 29 , 30 , 31 , 32 , 33 ] ( Table 2 ).…”
Section: Frontal Recess Cells’ Prevalence In Different Populationsmentioning
confidence: 99%
“…In regard to the anatomical terminology, authors have used different names for naming the cells surrounding the frontal drainage pathway that include frontal cells [ 24 , 28 ], frontal sinus cells [ 27 ], and frontal recess cells [ 25 , 29 , 30 , 31 ]. To avoid confusion to the readers, in this review we describe these cells as frontal recess cells throughout the manuscript.…”
Section: Frontal Recess Cells and Their Association With Sinusitismentioning
confidence: 99%